Analyzing Creativity In The Translations Of Hafiz’s Selected Poems - Dorri, Esmail (2018)
The present study aims at analyzing creativity in the translation of Hafiz’s selected poems. He was the 14th century Persian poet renowned for his collection of lyrics. The specific objectives of the study include comparing nine translations of Hafiz’s selected poems in order to identify creative translations and translators, investigating the ways of achieving creativity in poetry translation and identifying the creativity effects on the quality of translations. Scholars such as Jackobson (1960) believe that the translation of poetry is complicated as it involves creativity which he considers to be a key element in the translation of poetry; it is the creative dimension of translation that significantly emerged.